Effects of GS-967, GS-6615 and ranolazine on the responses of the rabbit aorta to adrenergic nerve stimulation - Mauricio, Maria Dolores; Jorda, Adrian; Guerra-Ojeda, Solanye; Vila, Jose M.; Valles, Soraya L.; Aldasoro, Martin (Frontiers in Physiology, 2026)
IntroductionIn the present study we aim to determine the effects of different inhibitors of the late sodium current (INa,late) on vascular responses to adrenergic stimuli, both endogenous and exogenous.MethodsThe study was performed using specific inhibitors of INa,late as GS-967, GS-6615 and Ranolazine (RAN). Rings from rabbit aorta were placed in organ baths chambers.ResultsElectrical Field Stimulation (EFS) (2, 4 and 8 Hz) induced frequency-dependent contractions that were abolished by tetrodotoxin, prazosin, or guanethidine (10−6 M). The intervention of INa,late was observed by incubating the aortic segments with GS-967, GS-6615 or RAN. Concentration–response curves to GS-967, GS-6615 or RAN were constructed in rings precontracted with noradrenaline, endothelin-1 or KCl with or without specific inhibitors (L-NAME, nimesulide, SC-560, verapamil, nifedipine, apamin or charybdotoxin). Contraction to noradrenaline were elicited in the absence or presence of INa,late inhibitors (GS-967, GS-6615 or RAN). EFS induced frequency-dependent contractions of rings, mediated by noradrenaline acting on α1-adrenoceptors. INa,late blockers GS-967 and GS-6615 reduced vasoconstriction induced by sympathetic nerve stimulation, effect reversed by charybdotoxin, implicating large-conductance Ca2+-activated K+ channels. RAN elicited an attenuation of nerve-induced vasoconstriction, with 20% of this effect mediated via large-conductance Ca2+-activated K+ channels. The predominant mechanism involved competitive antagonism of RAN at α1-adrenergic receptors.DiscussionThese findings suggest distinct mechanisms of action among INa,late blockers, highlighting the involvement of large-conductance Ca2+-activated K+ channels in GS-967 and GS-6615 effects, and a competitive α1-adrenoceptor antagonism for RAN. Taken together, our results indicate that GS-967, GS-6615 and RAN decrease vasoconstrictor responses due to both neural and noradrenaline-induced adrenergic stimuli. We can suggest that the use of GS-967, GS-6615 and Ranolazine may be interesting in clinical procedures involving hyperstimulation of the adrenergic nervous system.